COHORT STUDY OF THE NATIONAL HEALTH STRATEGY FOR THE PREVENTION AND CONTROL OF TUBERCULOSIS OF THE HUANCAVELICA REGIONAL HOSPITAL - Chenet Zuta, Manuel Enrique (2020)
The objective was to determine the result ofthe National Health Strategy for the Prevention andControl of Tuberculosis ESN-PCT of the RegionalHospital of Huancavelica, taking as an indicator thecondition of discharge of the patients who were treatedby it. The research was descriptive, the inductive -deductive method was used as a general method,and the descriptive, statistical and bibliographicmethods were used as specific methods. The designwas retrospective epidemiological non-experimental:a case-control cohort study. We worked with a censusconsidering the patients with BK (+) registered inthe DIRESA Huancavelica database for two years,whose number was 36. The technique used was thedocumentary analysis with its instrument, the cohortstudy format. approved in the technical standard ofthe tuberculosis health strategy. In the first year thescheme cohort study (1) had 36 registered patients,of which 94.44% were cured and 5.56% died. In thesecond year, the scheme cohort study (1) had 28registered patients, of which 92.86% were cured and3.57% died. It is concluded that the ESNPCT yieldedexcellent results since at the end of the treatment thepatients' discharge condition was clinically cured witha high percentage in relation to the deceased andthose who abandoned the treatment.